Neutronic analysis of effects of inboard materials on the size of a tokamak fusion reactor. (September 2021) - Hong, B.G.; Cho, W.
Highlights: Inboard materials play a key role in determining the size of the reactor. The reactor parameters were determined via coupled tokamak systems analysis. Optimal combination of multiplier and reflector can lead to small reactor. Abstract: The effects of inboard materials on the size of a tokamak fusion reactor were studied based on reactor system parameters determined through a coupled analysis of tokamak systems and neutron transport. With an inboard blanket, the shielding capability was the best for tungsten carbide (WC), showing a smaller reactor size than cases using other shield materials. Shield materials such as WC, borated steel (BS), and ferritic/martensite steel (FMS) showed improved neutron economy for tritium breeding in the blanket, which was attributed to neutrons reflected by tungsten (W) and steel (Fe). In a configuration with only an outboard breeding blanket, it was found that the tritium self-sufficiency requirement could be satisfied with an inboard blanket replaced by a neutron multiplier and/or reflector materials. Titanium carbide (TiC) showed the best neutron reflecting capability. With lead (Pb) as a neutron multiplier, neutron spectrum softening by a Pb multiplier enhanced the reflector performance and increased tritium breeding at the outboard blanket. Thus, an optimum combination of multiplier and reflector materials can lead to smaller reactor sizes than reactors with an inboard blanket.